Editorial Matter - Yinyang: Jurnal Studi Islam Gender dan Anak (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
this section for upload any editorial material, such as front cover, back cover, eratum, corigendum, and retraction.